Peningkatan Kemampuan Menulis Berita Melalui Media Gambar Berseri Mahasiswa Tingkat 1 Program Studi Diii Gizi Poltekkes Kemenkes Padang - Ayu Gustia Ningsih; Dwi Christina Rahayuninggrum (Universitas Batanghari Jambi, 2019)
Findings from the results of the author's interviews with Indonesian language lecturers as well as level 1 students of the D3 Nutrition Science Study Program of the Polytechnic of the Ministry of Health in Padang are, students have not been able to write news, because of the following things. First, they have the lack of students' ability in writing. Second, students are less able to develop the elements of building news. Third, ineffective learning media used by lecturers. Based on the aforementioned problems, the authors think it is important to carry out classroom action research aimed at improving the ability to write news with serial images of students of level 1 of the D3 Nutrition Science program at the Health Ministry of Health in Padang. The selection of this serial image media is thought to be appropriate for learning to write news, because through this image media students are motivated because the media can be touched, seen and observed. In addition, the use of image media is thought to be easy for students to understand so students will more easily express their ideas or ideas in writing news. This class was chosen because the ability to write news in learning is low when compared to other classes, this is evidenced by the acquisition of the results of the writing test exposition of semester I of the academic year 2017/2018. The type of this research is classroom action research with the research subject level 1 of the Nutrition D III Study Program with 39 students. The research was carried out in semester 2 of the 2018/2019 school year. Data collection tools used were student activity observation sheets and final tests. Data analysis techniques used are descriptive and analysis of learning outcomes. This research consisted of two cycles and each cycle was held twice. The results of the study in each cycle are pre-cycle with an average value of 70.87 students, the first cycle with an average value of 86.46 students and the second cycle 93.74, this shows student activity tends to increase. Furthermore, it was concluded that lectures on learning to write news with serial image media can increase the activity and learning outcomes of students in level 1 of the D III Nutrition Study Program of the Health Ministry of Health in Padang.